PELATIHAN DASAR-DASAR AKUNTANSI, KEWIRAUSAHAAN DAN PERPAJAKAN PADA PONDOK PESANTREN NURUL IHSAN - Zenabia, Tsarina; Dewi, Eka Kusuma; Saga, Baharuddin (Jurnal Abdi Citra, 2024)
Tri Dharma College is the three main tasks that must be fulfilled by the academic civilisation of college, one of the forms of implementation of the main task is the execution of devotion to the community (PKM). PKM activities are activities that include the application, development and dissemination of science. The activities of PKM form a collaboration of education and teaching between colleges and community partners. This time, the lecturer of the Accountancy Studies Program of the University of Pamulang organized a PKM at the Nurul Ihsan Pondok Pesantren in Tangerang South Banten. The implementation of the PKM is divided into three material sessions and is carried out by methods of presentation, training and discussion. At the end of the presentation session, questions were answered to the centers included with the award of the doorprize. The PKM activities are expected to complement the training science curriculum in which the centri not only have strong Islamic values but also accounting, entrepreneurship and taxation skills that are useful for self-development.